Two new spotted Chiloschista species (Orchidaceae: Aeridinae) from Bhutan - Gyeltshen, Nima (Universidad de Costa Rica, 2020)
Two new spotted species of Chiloschista from Bhutan are described, illustrated, and compared with similar species. The second of the new species has been misidentified in previous publications as C. lunifera and C. parishii, and a comparison between the three is provided. It is also compared with C. glandulosa, which is a distinctly smaller-flowered species from the coastal area of southwestern India, and with C. javanica from Indonesia. The latter species and C. parishii are easily distinguished from both new species by having hairs on the backside and along the margins of the sepals and petals, as opposed to having virtually glabrous to indistinctly micro-pubescent sepals and petals for the new species. Although many spotted Chiloschista species are superficially similar, the differences can be better observed when studying the internal morphology of particularly the glandular callosity in the saccate lip. The morphological differences are often minute and difficult to describe in words, but are more easily recognized when compared with illustrations and photographs. Key Words: Chiloschista glandulosa, C. javanica, C. lunifera, C. parishii, new Chiloschista